Perception of Social Entrepreneurship in Morocco: A Building Site That Is Just to Be Constructed - Rihihil, Abdallah; Tayane, SouÃ¢d; Gassemi, Karim; Zahouily, Mohamed (International Journal of Engineering and Technology, 2019)
Social entrepreneurship is a relatively new phenomenon that generates significant potential for economic and social transformation, minimizes inequality and promotes social bonds. Although Morocco is at the beginning of developing this type of activity and the necessary infrastructure associated with it, many initiatives have emerged thanks to social entrepreneurs acting in this direction. These entrepreneurs have demonstrated their ability to provide effective solutions to a wide range of economic, social and environmental issues. It is not just about creating for profitable businesses with social goals, but about building an entrepreneurial spirit and inspiring young people, especially women, to find innovative solutions to the daily problems they face.Â In order to measure the satisfaction and expectations of social entrepreneurs in the dynamism of the social and solidarity economy, we conducted a survey, through various regional territorial indicators, of the potentialities and constraints experienced by the region of Casablanca- Settat (Morocco).Â The objective of this study is to develop a barometer of social and territorial entrepreneurship, to build confidence in social entrepreneurs as to their ability to solve major societal problems. The survey revealed limited knowledge of social entrepreneurship among the general public. Recognition of their impact by the various stakeholders remains a major challenge to be addressed in order to better publicize the action of social entrepreneurs at a territorial and national level.